TU7.8 Pay Per View: Cost and Satisfaction of Virtual Video Clinics. (9th August 2022) - Clements, Caterina; Bezzaa, Sabrina; Graham, Gemma; Tharmarajah, Emmanuel; Jamal, Karim; Lewis, Trystan
Abstract: Aims: The Covid-19 pandemic necessitated use of video consultations to provide continued patient care. It is not clear if video clinics are well received by patients, or if they are cost efficient. We evaluate the benefits of video consultation and review the impact on waiting times and cost implications to a trust. Methods: 100 patients referred between January - December 2021 with gallstones were invited to complete a patient satisfaction questionnaire after initial clinic consultation. Patients were divided into three groups based on consultation type; face-to-face, telephone and video consultation (via the Attend Anywhere platform). Secondary outcome measures included time from referral to appointment, time to final outcome and cost implications. Results: 93 patients responded; 33 video, 30 face-to-face and 30 telephone consultations. Of these patients 62% were female and 38% male with an average age of 51 (25–84). Average time from referral was 22 days in the video cohort, 22 in the telephone cohort and 32 for face-to-face appointments. Of the video cohort, 44% were booked for cholecystectomy from initial consultation and 56% sent for further investigation. The conversion rate from video to face-to-face consultation was zero. 50% of respondents stated face-to-face consultations as their preferred method of future consultation, 49% of patients opted for video and 1% preferred telephone consultation. 79% reported increased satisfaction due to convenience of consultation. Conclusion: This study demonstrates video consultations decrease costs and waiting times. Patient satisfaction is comparable to in-person visit. Specific referral criteria and patient selection is essential to maximise the benefits of video consultations.